2015
DOI: 10.1007/s10530-015-0982-4
|View full text |Cite
|
Sign up to set email alerts
|

Broad and local-scale patterns of exotic earthworm functional groups in forests of National Wildlife Refuges of the Upper Midwest, USA

Abstract: The National Wildlife Refuge System is the world's largest network of lands set aside specifically for wildlife conservation. For refuge planners and managers tasked with maintaining ecological integrity and wildlife habitat, many uncertainties exist. In forests in the Upper Midwest, for instance, exotic earthworms are impacting ecosystem structure and function, but their community composition and effects on refuges is unknown. We examined the association of earthworm functional group abundance and community c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
2
2
0
Order By: Relevance
“…Whether measured in terms of biomass or density, earthworms were consistently more abundant on islands with campsites as compared to those without. This result corroborates the findings of previous studies showing that human activity influences the distribution and abundance of non-native earthworms (Hendrix et al, 2008;Shartell et al, 2015). These include correlations with road proximity (Cameron & Bayne, 2009) and boat launches (Cameron, Bayne & Clapperton, 2007) and their spread through use as fish bait (Keller et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…Whether measured in terms of biomass or density, earthworms were consistently more abundant on islands with campsites as compared to those without. This result corroborates the findings of previous studies showing that human activity influences the distribution and abundance of non-native earthworms (Hendrix et al, 2008;Shartell et al, 2015). These include correlations with road proximity (Cameron & Bayne, 2009) and boat launches (Cameron, Bayne & Clapperton, 2007) and their spread through use as fish bait (Keller et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…As we predicted, earthworms were most-likely to be present near roads. These findings are congruent with other studies that suggest that earthworms are generally found closer to roads, especially older roads, along forest edges, near logging sites, or near other human disturbances (Beausejour et al 2014, Bohlen et al 2004a, Cameron and Bayne 2009, Gundale et al 2005, Holdsworth et al 2007, Randsom et al 2015, Sackett 2012, Shartell et al 2015. In Maine, I interpret the fact that distance to roads is the only significant predictor in our model as evidence Forest size, forest composition, and pH were not statistically significant predictors for worm presence; however their inclusion in the best-fit model indicates that they are important factors in predicting the presence of earthworms at a site.…”
Section: Discussionsupporting
confidence: 91%
“…Epi-endogeic earthworms, consuming leaf litter and top mineral soil, were found in all land use types except in grasslands. Shartell et al (2015) [64] opined that epi-endogeic worms had strong association with human impacted habitats and ability to coexist with other functional groups. Anecic functional group of earthworms was not found in any of the land use types under the present study that were either degraded or highly disturbed.…”
Section: Discussionmentioning
confidence: 99%